Marketing Strategy for KSPSS BMT Dana Mentari Muhammadiyah Purwokerto Student Savings Products - Dinu Saadillah; Drajat Aji Saputra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
KSPPS BMT Dana Mentari Muhammadiyah Purwokerto is a financial institution that runs on a sharia system. The KSPPS BMT Dana Mentari Muhammadiyah company has many products, one of which is student savings. Every company, including financial companies, requires a marketing strategy, which is an important aspect to achieve targets. Marketing is a social and managerial process that involves individuals and groups getting what they need and want by creating, offering and exchanging valuable services with other parties. Marketing strategy is contained in four marketing mix positions, namely price strategy, promotion strategy, promotion strategy, place strategy and product strategy. To achieve marketing targets, you must consider the four marketing mixes. The method used in this research is qualitative with a descriptive analysis approach. The data collection techniques used were observation, interviews and documentation. The aim of this research is to find out the marketing strategy for KSPPS BMT Dana Mentari Muhammadiyah Purwokerto student savings. The results of this research show that KSPPS BMT Dana Mentari Muhammadiyah Purwokerto has a good marketing strategy for student savings products seen from qualified products, affordable prices, targeted promotions and strategic office locations. This is a factor in students using and choosing savings products at KSPPS BMT Dana Mentari Muhammadiyah Purwokerto.